MANAJEMEN STRATEGIK KOSHIKOI JAPANESE TRAINING CENTER DALAM MEMPERSIAPKAN TENAGA KERJA - Ayi Najmul Hidayat; Apriadi Manan Firman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The training organized by the Kashikoi Japanese Training Center is considered important because often formal educational institutions have not been able to produce graduates who are ready to work and compete, especially in the era of global competition, so that in order to face the era of globalization, prospective workers still need to be equipped with increased competence in order to be able to compete with other nations. . In order to achieve the vision and objectives of the Kashikoi Japanese Training Center, it is necessary to design a strategic plan to determine the vision, mission and objectives of the institution so that they can be achieved effectively and efficiently so that the direction of policies and program activities leads to the achievement of the vision, mission and goals that have been set. set. The purpose of this study is to obtain an overview of the strategic management of the Kashikoi Japanese Training Center in preparing the workforce. By using a qualitative descriptive research method, the results of the vision and mission research designed by the Kashikoi Japanese Training Center were obtained, namely to prepare a skilled and competitive workforce by utilizing the collaboration between the Governments of Indonesia and Japan. The Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) calculations show that the Kashikoi Japanese Training Center is in a very favorable situation. The role of the Kashikoi Japanese Training Center is to prepare Indonesian workers who will go to Japan through 3 (three) programs, namely pre-apprenticeship, tokutei gino and a school program to Japan .